Determination of Nectar Resources through Body Surface Pollen Analysis: A Study with the Stingless Bee Tetragonula iridipennis Smith (Apidae: Meliponini) in West Bengal, India - Bisui, Sourabh; Layek, Ujjwal; Karmakar, Prakash (Sociobiology, 2021)
Knowledge about floral resources is essential for bee management and conservation. Pollen analysis of honey is the most traditional method for determining the nectar resources of a bee species. However, the collection of honey samples is difficult in cavity-nesting natural stingless bee colonies. Furthermore, it is detrimental to the wild bee’s colony and may threaten their survivability. We analyzed adhered body surface pollen of incoming nectar foragers (which were smeared incidentally during nectar foraging) as an alternative method to determine nectariferous flora of Tetragonula iridipennis in West Bengal, India. By this method, we have identified 75 pollen types. The number of obtained pollen types was lower in the human-altered habitats of Midnapore city (44 pollen types) than the semi-natural habitats of Garhbeta (71 pollen types). Excluding a few pollen types of non-nectariferous plants, most of the pollen types came from nectariferous plants of both crop and non-crop species. Non-crop flowering plants (viz. Ailanthus excelsa, Borassus flabellifer, Eucalyptus tereticornis, Lannea coromandelica, Peltophorum pterocarpum, and Tectona grandis) provided a significant amount of nectar to the bee species and, therefore, play an important role in the conservation of the bee species.